Reducing the Schottky barrier height at the MoSe2/Mo(110) interface in thin-film solar cells: Insights from first-principles calculations - Mirhosseini, Hossein; Kiss, Janos; Roma, Guido; Felser, Claudia (Thin Solid Films, 2016)
We report on first-principles calculations of the properties of the MoSe2/Mo(110) interface. Due to mismatch between the lattice parameters of the two structures, different patterns can form at the interface. We have studied the formation energy and the band alignment of six patterns for the MoSe2 (0001)/Mo(110) interface and one pattern for the MoSe2 (1120)/Mo(110) interface. The MoSe2 (1120)/Mo(110) interface is more stable than the MoSe 2 (0001)/Mo(110) interface and in contrast to MoSe2 (0001)/Mo(110), no Schottky barrier forms at MoSe2 (1120)/Mo(110). Doping with Na modifies the band alignment at the interfaces. The Schottky barrier height decreases, provided that a Na atom occupies a Mo atom site in MoSe2 films.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Cu(In; Ga)Se; Interface; MoSe; Schottky barrier; Thin-film solar cell